Negotiating the racial and ethnic boundaries of citizenship: white South African migrants in the UK and their sense of belonging - Halvorsrud, Kristoffer (2014)
This PhD thesis is based on a qualitative interview study of white South Africans who have migrated to the UK in the post-apartheid era, focusing on their sense of belonging and ‘racial’/ethnic boundary-processes in society. With the increasing South African emigration in the post-apartheid era, the UK has been South Africans’ primary destination. Nevertheless, this migrant group has received relatively little scholarly attention. It could seem as though South Africans have been considered less interesting for research purposes, as their typical status as white and relatively privileged migrants appears to have made them better perceived by the British state apparatus and public than many ‘non-white’ and other disadvantaged migrants (Crawford 2011).